DEVELOPMENT OF A DIGITAL COMIC FOR FRACTION LEARNING IN JUNIOR HIGH SCHOOL STUDENTS - Muliawan, Nadia Fitri; Syamsuddin, Nuralam; Apriliani, Vina (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
Understanding fractions remains challenging for many junior high school students, especially in distinguishing numerators and denominators, identifying equivalent fractions, and converting contextual problems into mathematical models. Conventional learning media often lack interactive and engaging features, causing students to struggle with conceptual understanding. This study introduces a digital comic as an innovative and interactive learning medium designed to make fraction learning more contextual and appealing. The research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). The product, a digital comic in PDF format accessible online, was tested on seventh-grade students at SMP Negeri 9 Banda Aceh. Validation results showed high validity from media (85.90%), content (84.97%), and language experts (100%). Practicality assessments from teachers (93.75%) and students (93.43%) also indicated that the comic is highly practical. These findings highlight the novelty and effectiveness of integrating digital comics into mathematics learning, demonstrating that such media can enhance students’ motivation and conceptual understanding of fractions.